Oxidative Stress Biomarkers and Pathological Alterations Induced by Cryptosporidim Infection in Buffalo Calves at Assiut Governorate, Egypt - Mahran, Osman M.; Rateb, Mohammed H.; Abouel-Hassan, Lamiaa; Abd Allah, Elham Abdelsabour (Journal of Advanced Veterinary Research, 2020)
This study aimed to examine the histopathological changes and some biochemical parameters including oxidative stress indices during the course of a natural Cryptosporidium parvum infection in newborn buffalo calves. A total of 102 buffalo calves of 1-3 weeks of age, suffering from diarrhea were examined for the presence of C. parvum oocysts. Out of them, 16 buffalo calves were positive for C. parvum and 15 calves were free from Cryptosporidium infection and represented the control group. The histopathological study was also included two newly born buffalo calves that were died and proved to be positive for C. parvum oocysts. Intestinal and abomasal mucosa of infected calves showed villous atrophy and architectural abnormalities characterized by rounded edges, with markedly dilated glands filled with necrotic material, and numerous cryptosporidia at different stages of life cycle. Serum biochemical constituents revealed decreases (P < 0.05) in concentrations of total proteins (-14.94%), albumin (-17.22%), sodium (-7.532%), potassium (-16.02%) and chloride (-9.628%) when compared with healthy calves. There were increases (P < 0.05) in serum concentrations of malondialdehyde (62.524%) and total peroxides (30.31%). In contrast, there were an inhibition (P < 0.05) in serum concentrations of total antioxidant capacity (-35.49%) and the activity of superoxide dismutase (-30.43%) in comparison with the control group. Pearson’s correlation coefficients (r) and linear regression (R2) analysis (n = 16) showed that TPX was inversely correlates with albumin (r=0.61, R2=0.43, P<0.001) and sodium (r=0.67, R2=0.48, P<0.001) concentration in serum of C. parvum infected calves. It can be concluded that, Cryptosporidiosis had an adverse effect on biochemical parameters with increased reactive oxygen metabolites and lipid peroxide production in infected buffalo calves, which may be responsible for tissue damage and villus atrophy in infected calves.